Fight and Flight: Evidence of Aggressive Capitulation in the Face of Fear Messages from Terrorists. Issue 6 (23rd April 2014) - Iyer, Aarti; Hornsey, Matthew J.; Vanman, Eric J.; Esposo, Sarah; Ale, Shalini
Abstract : In an era of digital technology and the Internet, terrorists can communicate their threats directly to citizens of Western countries. Yet no research has examined whether these messages change individuals' attitudes and behavior or the psychological processes underlying these effects. Two studies (conducted in 2008 and 2010) examined how American, Australian, and British participants responded to messages from Osama bin Laden that threatened violence if troops were not withdrawn from Afghanistan. Heightened fear in response to the message resulted in what we call "aggressive capitulation, " characterized by two different group‐protection responses: (1) submission to terrorist demands in the face of threats made against one's country and (2) support for increased efforts to combat the source of the threat but expressed in abstract terms that do not leave one's country vulnerable. Fear predicted influence over and above other variables relevant to persuasion. Theoretical and practical implications are discussed.